PENILAIAN INTENSIFIKASI DAN EKSTENSIFIKASI UNTUK MENINGKATKAN PENDAPATAN ASLI DAERAH - Oktifauziah, Fierly (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2014)
The aim this research is to find out and to analyze how much the achievement level of the original local revenuein the city of Surabaya then to know and to analyze all efforts which have been done by the department ofrevenue and financial management in improving local revenue intensively and extensively; as well as to knowand to analyze some factors which which both hold up and support intensively and extensively to the originallocal revenue of Surabaya city. Qualitative research is type of reseach which is The data analysis technique isusing qualitative method. The result of this research is: (1) local tax gives bigger contribution when it iscompared to local retribution to the original local revenue, (2) during the years of 2009-2012 the realization oforiginal local revenue which was generated by the department of revenue and financial management did notmeet the target, (3) some factors are intensively and extensively supported, they are, (a) proactive system whichmeans the officers performs billing collection to the delinquent tax; (b) sending a warning letter payment to thenearest UPTD office (local tax office), (d) improving counseling activity to the society, (4) some factors holdingup intensively and extensively are, (a) the lack of knowledge of the society about the payment procedure, (b)incapable in determining sanction.Keywords: intensive, extensive, original local revenue, and local autonomy.